Bali Bombing and the Erosion of the Legality Principle: A Juridical Analysis of the Application of Retroactive Law in Countering Terrorism in Indonesia: Ledakan Bom di Bali dan Erosi Prinsip Legalitas: Analisis Hukum tentang Penerapan Hukum Retroaktif dalam Pemberantasan Terorisme di Indonesia - Dheni Anugerah Prasetya; Rohadhatul Aisy (Indonesian Journal of Counter Terrorism and National Security, 2024)
The Bali Bombing I incident in 2002 became an important turning point in counterterrorism in Indonesia. However, the absence of specific regulations related to terrorism during the incident forced the government to issue Perppu No. 1 Year 2002, which was then applied retroactively. This retroactive application of criminal law raises serious issues in the national legal system, especially against the principle of nullum delictum nulla poena sine praevia lege poenali, which is a fundamental principle in the rule of law. This article aims to analyze the validity of the implementation of the Perppu from a normative juridical perspective, as well as to assess whether the argument that the crime of terrorism is an "extraordinary crime" can be used as a justification for retroactive law. By examining national legislation, the constitution, as well as international human rights law instruments such as the ICCPR, this article finds that the government's action has the potential to violate the principle of legality and open space for unconstitutional legal practices in the future. Therefore, strengthening the principles of the rule of law should be the main foundation in drafting anti-terrorism regulations in Indonesia.